(untitled) (Balneo and PRM Research Journal, 2025)
Low back pain is one of the major public health problems, with approximately 1 in 3 adults experiencing an episode of low back pain during their lifetime. The aim of this study was to evaluate the effect on pain and physical function of a therapeutic protocol including analgesic electrotherapy, lumbar deconstrictor manual therapy and kinetic therapy and the superinductive magnetic field therapy. Patients were divided into two groups of 20 and 20 respectively. Group 1 was treated with the conventional protocol, while the second group received in adition the superinductive magnetic field therapy. Pain was assessed by VAS scale at admission and every 2 days, and functional deficit was assessed by the Fingertips to floor (FTF) test at admission, at 6 days and at discharge at 12 days. The Activities of Daily Living (ADL) scale was also used to assess physical function at admission and discharge. 40 patients (24 female, 16 male), average age 61 years ( ± 5.7), average BMI of 32.11± 7.38 SD, kg participated and their data were analyzed. An average percentage decrease in VAS was noticed after the 12 days of treatment of 67% for group1 and of 88% for group 2. The deficit in FTF was also better in group 2 (FTF= 16+5cm ) compared to FTF=22+3 in the control group. On ADL assessment, no significant differences were noted. Superinductive magnetic field therapy is effective in the treatment of low back pain relieving pain syndrome and improving physical function.